Facilitators to Accessibility of HIV/AIDS-Related Health Services among Transgender Women Living with HIV in Yogyakarta, Indonesia - Nelsensius Klau Fauk; Maria Silvia Merry; Theodorus Asa Siri; Fabiola Tazrina Tazir; Mitra Andhini Sigilipoe; Kristin Oktanita Tarigan; Lillian Mwanri (AIDS Research and Treatment)
The study aimed to explore facilitators or enabling factors that enhance accessibility (defined as the opportunity to be able to use) to HIV/AIDS-related health services among HIV positive transgender women, also known as Waria in Yogyakarta, Indonesia. A qualitative study employing one-on-one in-depth interviews was conducted from December 2017 to February 2018. Participants were HIV positive Waria recruited using purposive and snowball sampling techniques. Data were analysed using the framework analysis for qualitative research. The findings showed that participants’ knowledge of HIV/AIDS and the availability of HIV/AIDS-related health services were enablers to the services accessibility. Emotional support from fellow Waria displayed in various ways, such as kind and caring attention, attentive listening, and encouraging words, was an important social support that played a role in supporting Waria’s accessibility to the services. HIV/AIDS-related health service information shared personally or jointly by fellow Waria and instrumental support including helping each other to collect antiretroviral (ARV) from hospitals or community health centres, contacting ambulance in emergency situations, accompanying each other to health service facilities, and helping those without the health insurance to receive free health services were also the social support enabling accessibility to the services among the study participants. Appraisal support such as providing constructive feedback and affirmation was another enabling factor to Waria’s accessibility to the services. The findings indicate the needs to broadly disseminate information and educate Waria populations and their significant others about HIV/AIDS and related health services to raise their awareness of HIV/AIDS and acceptance of HIV/AIDS positive individuals. Educating and broadly disseminating this information in other settings in the country will also increase accessibility to the HIV/AIDS services among Waria, their families, and communities addressing the currently existing inequities in health. The findings also reinforce the importance of the establishment of Waria peer-support groups within Waria communities and the involvement of Waria in HIV/AIDS activities and programs, which may increase their awareness of HIV/AIDS, and accessibility to HIV/AIDS-related health services.